SYNTHETIC QUINAZOLINONES AS NEW ANTILEUKEMIC AGENTS - Giorgio Antoniolli; Keli Lima; João Agostinho Machado-Neto; Carmen Silvia Passos Lima; Fernando Coelho (Hematology, Transfusion and Cell Therapy)
Introduction/Justification: Acute leukemias are aggressive malignancies characterized by the uncontrolled proliferation of hematopoietic progenitor cells in the bone marrow, leading to impaired production of normal blood cells. Nitrogen heterocycles have attracted the attention of researchers from various fields, with an extensive list of different biological activities. Among the heterocycles, quinazolines stand out, which have been widely investigated for the development of new drugs. Objectives: Evaluation of the anticancer activity of quinazolinones against acute leukemic cell lines. Materials and Methods: The quinazolinones (A1-A20) were synthesized in the Laboratory of Synthesis of Natural Products and Drugs (Institute of Chemistry, Unicamp). In total 2 × 104 cells of T cell acute lymphoblastic leukemia (T-ALL), Jurkat, and acute promyelocytic leukemia (APL), NB4, per well were seeded in a 96-well plate in the appropriate medium in the presence of vehicle or different concentrations of compounds (ranged from 0.8 to 50 μM) for 72 h. Leukemic cells were exposed to the presence of vehicle or different concentrations of compounds (ranged from 0.8 to 50 μM) for 24, 48 and 72 h. Next, 10 μl methylthiazoletetrazolium (MTT, Sigma-Aldrich) solution (5 mg.mL-1) was added and incubated at 37°C, 5% CO2 for 4 h. The reaction was stopped using 100 μL 0.1 N HCl in anhydrous isopropanol. Cell viability was evaluated by measuring the absorbance at 570 nm. IC50 values were calculated using nonlinear regression analysis in GraphPad Prism 5 (GraphPad Software, Inc., San Diego, CA, USA). SwissADME and pkCSM software were used to predict the properties of the compounds. Results: Of the compounds synthesized, A1, A2, A3 and A4 showed antileukemic activity. Compounds A1 and A4 were the least cytotoxic for both cell lines. A2 showed strong activity against Jurkat cells. The best compound in the study, A3, showed strong activity against both Jurkat and NB4 cells. In the investigation of apoptosis by flow cytometry, the baseline cell viability was greater than 85%, which indicates a good quality cell culture and reliability in the data obtained. A2 showed greater efficacy, but still limited in Jurkat cells compared to NB4 cells. Compound A4 was the most effective in both models tested. For Log P (consensus), all the molecules are within the molecular filters, with A3 having the highest value, 3.79. The final analysis of all those described in this study indicates that all the quinazolinones synthesized meet the parameters for oral bioavailability. Conclusion: In this study, we prepared a series of quinazolinones that exhibited antiproliferative activities in T-ALL and APL. The most promising result of the study was A3 for both T-ALL and APL cells, respectively. In the analysis of apoptosis by flow cytometry, the highlight was also A3, which was the most effective against both cell lines.